Penggunaan Media Interaktif Berbasis PowerPoint untuk Meningkatkan Pemahaman Materi Pendidikan Agama Islam di SMPN 4 Bonai Darussalam - Supiarti, Tri; Masrida, Masrida (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This study aims to improve students’ understanding of Islamic Religious Education (PAI) material through the use of interactive PowerPoint-based media at SMPN 4 Bonai Darussalam. The research employs the Classroom Action Research (CAR) method using the Kemmis and McTaggart model, which consists of four stages in each cycle: planning, implementation, observation, and reflection. The subjects of this study were students of [mention class], with data collected through comprehension tests, observations, questionnaires, and interviews. The results indicate that the implementation of interactive PowerPoint media increased student participation in learning and clarified PAI concepts being taught. The pre-test and post-test results showed a significant improvement in students’ understanding after using interactive media. Furthermore, the questionnaire and interview findings revealed that most students felt more motivated and found it easier to understand the material through visual displays and animations in PowerPoint. Thus, the use of interactive PowerPoint-based media has been proven effective in enhancing students’ comprehension of PAI material. This study recommends that teachers integrate more technology into their teaching strategies to improve the effectiveness and engagement of classroom learning.